Cellulose Nanofiber Nanosheet Multilayers by the Langmuir-Blodgett Technique - Bashar, M Mahbubul; Ohara, Hiroaki; Zhu, Huie; Yamamoto, Shunsuke; Matsui, Jun; Miyashita, Tokuji; Mitsuishi, Masaya (Langmuir, 2019)
We describe a systematic approach for producing cellulose nanofiber (CNF) nanosheets using the Langmuir-Blodgett (LB) technique. The CNFs were obtained from sulfuric acid hydrolysis of commercially available microfibrillated cellulose. Needle-like CNFs, negatively charged by grafted sulfate groups, were maintained at the air-water interface, assisted by amphiphilic polymer, poly( N-dodecyl acrylamide) (pDDA). The CNFs produced a stable monolayer. The surface pressure increased steadily with a high collapse pressure of 50 mN m when spread with formic acid and pDDA. The composite monolayers were transferred onto solid substrates as Y-type LB films using a vertical dipping method. Upstroke and downstroke transfer ratios of the films were, respectively, unity and 0.88, indicating that full coverage was achieved by the monolayer even for more than 200 layers. Results obtained using atomic force microscopy, Fourier transform infrared, and X-ray photoelectron spectroscopy showed that CNF nanosheets possess well-defined layer structures with average monolayer thickness of 5.3 nm. The relative amount of CNFs in the nanosheets was calculated as 62.6 wt % using the quartz crystal microbalance technique. The as-prepared nanosheets are optically transparent to visible light and have high hydrophobicity. In fact, the nanosheet transparency was higher than 88% at 600 nm wavelength for 24 layers. A miniscule amount of pDDA enables demonstration of free-standing CNF nanosheets with 1 cm width and 45.6 nm thickness (23 layers).